2016
DOI: 10.1111/rda.12756
|View full text |Cite
|
Sign up to set email alerts
|

Expression of retinoic acid‐metabolizing enzymes, ALDH1A1, ALDH1A2, ALDH1A3, CYP26A1, CYP26B1 and CYP26C1 in canine testis during post‐natal development

Abstract: Mammalian spermatogenesis involves highly regulated temporal and spatial dynamics, carefully controlled by several signalling processes. Retinoic acid (RA) signalling could have a critical role in spermatogenesis by promoting spermatogonia differentiation, adhesion of germ cells to Sertoli cells, and release of mature spermatids. An optimal testicular RA concentration is maintained by retinaldehyde dehydrogenases (ALDHs), which oxidize RA precursors to produce RA, whereas the CYP26 class of enzymes catabolizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…However, investigations of how and where atRA is produced to drive these processes have been complicated by gaps in our knowledge of the enzymes responsible for atRA biosynthesis. Although the expression of ALDH1A1 residing within adult Sertoli cells may contribute to the biosynthesis of atRA driving the premeiotic transitions, several groups have provided evidence to suggest that ALDH1A2 residing within the meiotic and postmeiotic germ cells is the major isomer involved [31,32,38,45]. In this report, we have examined for the first time the in vivo contribution of ALDH1A2 to postnatal testicular atRA levels using two complementary genetic approaches.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, investigations of how and where atRA is produced to drive these processes have been complicated by gaps in our knowledge of the enzymes responsible for atRA biosynthesis. Although the expression of ALDH1A1 residing within adult Sertoli cells may contribute to the biosynthesis of atRA driving the premeiotic transitions, several groups have provided evidence to suggest that ALDH1A2 residing within the meiotic and postmeiotic germ cells is the major isomer involved [31,32,38,45]. In this report, we have examined for the first time the in vivo contribution of ALDH1A2 to postnatal testicular atRA levels using two complementary genetic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…We utilized a previously published WIN7D + RA synchrony protocol with minor modifications [44,45]. Briefly, 2 dpp 129/B6 male mice were pipette fed 100 mg/kg/bw (body weight) WIN (gift from Dr John Amory) daily for 7 days, given an atRA injection on day 9 and maintained on one of the following treatment regimens during the injection recovery: (1) 1% gum tragacanth (WIN7D + RA), (2) 150 mg/kg/bw WIN (WIN7D + RA + WIN), (3) 25 mg/kg/bw of HYD (Sigma-Aldrich, H1753) (WIN7D + RA + HYD), or (4) 150 mg/kg/bw WIN and 25 mg/kg/bw HYD (WIN7D + RA + WIN/HYD) (Supplemental Figure S2).…”
Section: Win Hydralazine Treatments and Atra Injectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…1113 ALDH1A1 is expressed in sertoli cells while ALDH1A2 is found in spermatogonia, spermatids, and spermatocytes. 12,14 ALDH1A2 is regarded as the primary RA-synthesizing enzyme in mammalian spermatogenesis, 15 and ALDH1A2 levels are significantly reduced in the testicular tissue of infertile men. 16 Therefore, ALDH1A2 is considered as a promising target for the development of nonhormonal male contraceptives.…”
mentioning
confidence: 99%
“…ALDH1A2 as substrates can recognize free retinal and cellular retinol-binding protein-bound retinal. It mainly metabolizes octanal and decanal but does not metabolize citral, benzaldehyde, acetaldehyde, and propanal efficiently [36, 37]. Shou S et al [38] revealed that defects in IPCD and digit separation in Hoxa13 mutant mice may be partly caused by reduced levels of RA signaling stemming from a loss in the direct regulation of Aldh1a2.…”
Section: Discussionmentioning
confidence: 99%